2020
DOI: 10.1186/s12944-020-01283-x
|View full text |Cite
|
Sign up to set email alerts
|

Chia (Salvia hispanica)-supplemented diet ameliorates non-alcoholic fatty liver disease and its metabolic abnormalities in humans

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is a public health problem lacking an approved pharmacological treatment. Omega-3 fatty acids have shown to reverse NAFLD. Chia is a seed rich in α-linolenic acid (ALA), antioxidants, and fiber; therefore, it could be useful to treat NAFLD. Methods: In a single arm experimental design study, the effect of 25 g/day of milled chia was assessed in 25 patients with NAFLD. After two weeks of dietary stabilization (basal condition) and eight weeks of a chiasupple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…16,17 Several studies on humans and experimental animals, including our group, have shown that the dietary intake of bioactive components from chia seeds is related to the protective effects on the liver and plasma oxidative stress. 11,[18][19][20][21][22] Therefore, the evaluation of potential functional foods that may improve the antioxidant system efficacy or alleviate reactive oxygen species formation could be a strategy to prevent or ameliorate disorders related to MS.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Several studies on humans and experimental animals, including our group, have shown that the dietary intake of bioactive components from chia seeds is related to the protective effects on the liver and plasma oxidative stress. 11,[18][19][20][21][22] Therefore, the evaluation of potential functional foods that may improve the antioxidant system efficacy or alleviate reactive oxygen species formation could be a strategy to prevent or ameliorate disorders related to MS.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Medina-Urrutia et al involving 25 patients with NAFLD and insulin resistance, dietary supplementation with ground chia seeds at a dose of 25 g/d for 8 weeks resulted in a reduction in body weight (median-.4%) and waist circumference. In addition, reductions in total cholesterol (from 4.8 to 4.6 mmol/L) and triglyceride levels (from 1.9 to 1.6 mmol/L) were observed in the intervention group [90].…”
Section: Clinical Studiesmentioning
confidence: 90%
“…S. hispanica provides a balanced amount of nutrients composed of insoluble fibers, proteins with a high quality of amino acids, high content of antioxidants, such as phenolic compounds such as caffeic acid, chlorogenic acid, and quercetin. Many studies described its potential for treating obesity [ 35 ], diabetes [ 35 , 36 , 37 ], hypertension [ 36 ], cardiovascular disease [ 37 ], NAFLD [ 38 ], hyperlipidemia [ 39 ], inflammation and oxidative stress [ 40 , 41 ].…”
Section: Lamiaceae: Bioactive Propertiesmentioning
confidence: 99%
“…Moreover, chia seeds seem to play a cardioprotective activity in normalizing the systolic blood pressure [ 45 ] ( Table 2 ). In a clinical trial a single arm experimental study investigated the effects of the daily intake (25 g/day) of chia seeds by 25 patients with NAFLD, showing a decrease in body weight, total Chol, non-HDL-Chol, and circulating free fatty acids (FFA) [ 38 ]. On the other hand, a double-blind, randomized, controlled trial with two parallel groups of 77 obese patients with T2DM [ 35 ] indicated the beneficial potential of chia seeds in promoting weight loss, and improving obesity-related risk factors such as a decrease in c-reactive protein (CRP) and an increase in plasma adiponectin.…”
Section: Lamiaceae: Bioactive Propertiesmentioning
confidence: 99%